Perbandingan indeks plak setelah konsumsi buah apel fuji (Malus pumila) dan buah apel manalagi (Malus sylvestris mill) pada anak usia 9 dan 10 tahun di SD Negeri 1 Dalung - Dik Megaputri Handayani; I Dewa Made Sukrama; L.W. Ayu Rahaswanti (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: Primary prevention of oral health problems need to be carried by applying the habit of plaque control to the children. Plaque control can be done naturally by chewing solid and fibrous food, such as apples. Objective: The aim of this study was to determine the plaque index before and after chewing Manalagi and Fuji apples. Methods: This study is an experimental research which used Pre-Post Test Control Group Design on children aged 9 to 10 years old. The sampling technique was using simple random sampling on 32 children and divided into 2 groups. Group 1 was chewing 100 grams of Fuji apples as the control group and group 2 was chewing 100 grams of Manalagi apples as the tested group. Results: The result from Paired Sample T-test shows that there was a significant difference of mean plaque index before and after chewing Fuji apples and Manalagi apples (p<0,05). The result from Independent Sample T-test shows that there was a significant difference of mean plaque index value between the group who was chewing Manalagi apples and group who was chewing Fuji apples (p<0,05). Conclusion: The conclusion of this study is that both of chewing Fuji apples and Manalagi apples are effective in reducing plaque accumulation, where chewing Manalagi apples shows higher efficacy in reducing plaque accumulation compared with chewing Fuji apples.